Correlation between Prostate-Specific-Antigen (PSA) Level and Prostate Volume in Benign Prostatic Hyperplasia at Bhayangkara Hospital Mataram - Krisna, Daniel M; Maulana, Akhada; Kresnoadi, Erwin (Journal of Medicine and Health, 2017)
Prostate enlargement is the most quality of life-impacted problem in elderly. Proper diagnoses and prostate volume prediction are important in considering the best treatment. PSA is a glycoprotein specifically secreted by prostate glands and influenced by various condition, such as Benign Prostatic Hyperplasia (BPH). The aim of this study is to identify the correlation between PSA serum level and prostate mass volume. This was a descriptive study with cross-sectional design that conducted at Bhayangkara Hospital Mataram on April 2015. Data were analyzed using Pearson correlation test and multiple regression logistic, to determine the relationship between PSA serum levels and prostate mass volume. The average PSA level was 34,62 ng/mL (1,82-30,70 ng/mL), and the average prostate mass volume were 72,57cc. There was correlation between PSA serum levels with prostate mass volume ( r = 0,384, p = 0,815). Conclusion, there is a relationship between PSA levels with prostate volume in BPH patients in Bhayangkara Mataram hospital.Keywords: Bhayangkara Hospital Mataram, BPH, prostate volume, PSA